Depiction of Ishana with a bull - Temples of India Project Team (Jio Institute, 2024)
The four-armed Ishana is depicted with a bull, his sacred companion. In his upper right hand, he holds a trishula (trident), while his upper left-hand grasps a sarpa (serpent). His lower right-hand makes a varada hasta (boon-giving gesture) and holds an akshamala (rosary), while his lower left hand carries a kamandalu (water pot).